A local regulatory network in the testis mediated by laminin and collagen fragments that supports spermatogenesis. (4th May 2021) - Li, Linxi; Li, Huitao; Wang, Lingling; Bu, Tiao; Liu, Shiwen; Mao, Baiping; Cheng, C. Yan
Abstract: It is almost five decades since the discovery of the hypothalamic-pituitary-testicular axis. This refers to the hormonal axis that connects the hypothalamus, pituitary gland and testes, which in turn, regulates the production of spermatozoa through spermatogenesis in the seminiferous tubules, and testosterone through steroidogenesis by Leydig cells in the interstitium, of the testes. Emerging evidence has demonstrated the presence of a regulatory network across the seminiferous epithelium utilizing bioactive molecules produced locally at specific domains of the epithelium. Studies have shown that biologically active fragments are produced from structural laminin and collagen chains in the basement membrane. Additionally, bioactive peptides are also produced locally in non-basement membrane laminin chains at the Sertoli-spermatid interface known as apical ectoplasmic specialization (apical ES, a testis-specific actin-based anchoring junction type). These bioactive peptides are derived from structural laminins and/or collagens at the corresponding sites through proteolytic cleavage by matrix metalloproteinases (MMPs). They in turn serve as autocrine and/or paracrine factors to modulate and coordinate cellular events across the epithelium by linking the apical and basal compartments, the apical and basal ES, the blood-testis barrier (BTB), and the basement membrane of the tunica propria. The cellular events supported by these bioactive peptides/fragments include the release of spermatozoa at spermiation, remodeling of the immunological barrier to facilitate the transport of preleptotene spermatocytes across the BTB, and the transport of haploid spermatids across the epithelium to support spermiogenesis. In this review, we critically evaluate these findings. Our goal is to identify research areas that deserve attentions in future years. The proposed research also provides the much needed understanding on the biology of spermatogenesis supported by a local network of regulatory biomolecules.